The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2040620720955000
|View full text |Cite
|
Sign up to set email alerts
|

Current and novel therapies for the prevention of vaso-occlusive crisis in sickle cell disease

Abstract: Individuals with sickle cell disease (SCD) are living further into adulthood in high-resource countries. However, despite increased quantity of life, recurrent, acute painful episodes cause significant morbidity for affected individuals. These SCD-related painful episodes, also referred to as vaso-occlusive crises (VOCs), have multifactorial causes, and they often occur as a result of multicellular aggregation and vascular adherence of red blood cells, neutrophils, and platelets, leading to recurrent and unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…Beneficial effects include the induction of fetal hemoglobin (HbF) for inhibiting erythrocyte adhesion, conceivably ensuring nitric oxide donor bioavailability; myelosuppression (resulting in the reduced availability of leukocytes, reticulocytes, and platelets) and reduced frequency of acute pain; and alleviation of acute chest syndrome, reduced hospital admissions, and reduced blood transfusions. It may also protect against progressive organ damage, including nephropathy [47,53]. Moreover, clinical trials in infants and toddlers have shown very promising results [12].…”
Section: Scd Management Approaches Other Than Hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects include the induction of fetal hemoglobin (HbF) for inhibiting erythrocyte adhesion, conceivably ensuring nitric oxide donor bioavailability; myelosuppression (resulting in the reduced availability of leukocytes, reticulocytes, and platelets) and reduced frequency of acute pain; and alleviation of acute chest syndrome, reduced hospital admissions, and reduced blood transfusions. It may also protect against progressive organ damage, including nephropathy [47,53]. Moreover, clinical trials in infants and toddlers have shown very promising results [12].…”
Section: Scd Management Approaches Other Than Hsctmentioning
confidence: 99%
“…Gene-modified HSPC graft repopulates the hematopoietic stem compartment, producing genetically corrected RBC progeny. Sickle HSPCs can be genetically modified through zinc finger nucleosomes (ZFNs), transcription activator-like effector nucleases (TALENs), or clustered regularly interspaced short palindromic repeats/CRISPR-associated nuclease 9 (CRISPR/Cas9) techniques (NCT03745287) [47][48][49][50].…”
Section: Engineered Stem Cell Approach For Scdmentioning
confidence: 99%
“…Three new drugs have been approved in the recent years: L-glutamine, voxelotor, and crizanlizumab. 2 Importantly, <200 individuals were treated with each medication at the approved dose prior to approval. Further, these clinical trials restricted the inclusion of people with SCD who had significant cardio renal disease.…”
mentioning
confidence: 99%
“…In addition to pain management and routine acquisition of prescription medications, such as Hydroxyurea (SCD-modifying agent) and opioid analgesics, individuals with SCD may need transfusion therapy (Telen et al, 2019). They also experience complications that include acute chest syndrome, infections, stroke, and chronic organ impairment (Abboud, 2020; Osunkwo et al, 2020). Consequently, individuals with SCD require thorough assessments and frequent monitoring.…”
mentioning
confidence: 99%